Adult asthma is associated with an increased risk of herpes zoster: A population-based cohort study. (16th March 2017) - Peng, Yi-Hao; Fang, Hsin-Yu; Wu, Biing-Ru; Kao, Chia-Hung; Chen, Hsuan-Ju; Hsia, Te-Chun; Liao, Wei-Chih
ABSTRACT: Objective : The objective of this study was to determine whether a new diagnosis of asthma is associated with a later diagnosis of herpes zoster (HZ) in a nationwide, retrospective, non-age limited, population-based cohort. Methods : We used data from the National Health Insurance Research Database in Taiwan. The asthma group consisted of all 40 069 patients in the database with newly diagnosed asthma and using asthma medications from 2000 through 2005. The nonasthma group comprised 40 069 age- and sex-matched patients without any asthma diagnosis. Cox proportional hazards regression analysis was applied to calculate the hazard ratio of HZ in the patients with asthma relative to those without asthma. Results : During a mean follow-up period of 8.77 years, the risk of HZ was 1.48-fold higher in the asthma group compared with that in the nonasthma group after adjustment for sex, age, comorbidities, inhaled and systemic corticosteroid use, and annual outpatient department visits to dermatologists. Additional stratified analyses revealed that the risk of HZ was significantly higher in patients of both sexes and those aged older than 21 years. Conclusions : Newly diagnosed adult patients with asthma have a significantly higher risk of developing HZ than do those without asthma.